Monthly Variation of Phytoplankton Composition in Sarawak River Estuary - Wan Nurul Nadiah, Binti Wan Rosdan (Universiti Malaysia Sarawak (UNIMAS), 2014)
The phytoplankton composition with selected physico-chemical parameters were studied in the estuary of Sarawak River. One sampling point from the estuary of Sarawak River was chosen and was sampled for four months from December 2013 to March 2014. The water samples collected were analysed for chlorophyll-a and nutrients while the phytoplankton samples were collected to determine the cell abundance. The phytoplankton samples have shown that the diatoms group dominated in all samplings followed by the dinoflagellates group and other phytoplankton. There were 22 genera of phytoplankton identified which are 18 genera from diatoms, 1 genus from dinoflagellates and 3 genera from other phytoplankton. The physico-chemical parameters such as temperature, turbidity, pH, dissolved oxygen and salinity have affecting the phytoplankton distribution in the water column. The turbidity and pH shows an inversely relationship with the cell density whereas the dissolved oxygen exhibit an increase when the cell density increase. Temperature and salinity has shown least obvious trend when compared to the cell density.